2020
DOI: 10.3855/jidc.11938
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of antibiotic misuse among Chinese children in developed and less developed provinces

Abstract: Introduction: Antimicrobial resistance is a global health crisis and primarily caused by antibiotic misuse. Antibiotic misuse among children is particularly concerning, and its prevalence may vary from region to region in China with different development levels. Methodology: Zhejiang and Shaanxi were selected to represent developed and less developed provinces in China, respectively. Data of 2924 parents in Zhejiang and 3355 parents in Shaanxi whose children were 0-13 years old were collected through mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 46 publications
0
37
0
Order By: Relevance
“…In the current study, the general population refers to patients and people that are potential patients, for example, residents, the elderly, parents, etc. Prophylactic use of antibiotics refers to the behavior of people taking antibiotics to prevent common infectious diseases, such as the cold or flu, which are mainly non-indicated diseases [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the current study, the general population refers to patients and people that are potential patients, for example, residents, the elderly, parents, etc. Prophylactic use of antibiotics refers to the behavior of people taking antibiotics to prevent common infectious diseases, such as the cold or flu, which are mainly non-indicated diseases [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…The likelihood of being prescribed with antibiotics for presumed self-limiting illnesses during an outpatient clinic visit varied from 53.3% 13 to 94.5% 14 in mainland China and 17 to about 50% 18 of participants prescribed with antibiotics were administered them through intravenous infusion. [17][18][19] Six studies investigated how patients' socioeconomic backgrounds might influence antibiotic prescribing 13 14 17 20-22 and among them, two identified patients' antibiotics-related knowledge as a determinant.…”
Section: Clinical Settings Antibiotic Prescriptions For Presumed Selfmentioning
confidence: 99%
“…Previous studies [ 15 , 16 ] have also shown the non-prescription antibiotic rates at community pharmacies for adult acute URTI without population-based data. In addition, the previous population-based surveys only limited to university students [ 14 , 17 ] or children [ 18 ]. These studies have highlighted the seriousness of the non-prescribed and injudicious use of antibiotics, as well as high rate of antibiotic use for cough.…”
Section: Introductionmentioning
confidence: 99%